PERANAN STRUKTUR MODAL MEMODERASI, HUBUNGAN CORPORATE SOCIAL RESPONSIBILITY DAN PERPUTARAN MODAL KERJA TERHADAP NILAI PERUSAHAAN - Fahira, Nabila Maulia; Sugiyanto, Sugiyanto (Universitas Jakarta Internasional, 2024)
This research is quantitative research, the data used is secondary data in the form of financial reports. This research aims to analyze the influence of corporate social responsibility (CSR) and working capital turnover on company value and look at the moderating role of capital structure in this relationship. CSR is one of the company's strategies to improve reputation and financial performance, while working capital turnover reflects the efficiency of managing current assets. Capital structure can function as a moderating variable that influences the relationship between CSR, working capital turnover, and company value. This research uses data from financial sector companies listed on the Indonesia Stock Exchange (BEI) in the 2019-2023 period. The analysis technique used is panel data regression with a moderated regression analysis (MRA) approach. The research results show that CSR has a positive effect on company value, while working capital turnover does not have a significant effect on company value. However, capital structure does not moderate the relationship between CSR and company value and the relationship between working capital turnover and company value. The results of this research provide implications for companies to pay more attention to CSR policies and working capital management in increasing company value. Additionally, investors can consider these variables in making investment decisions.